Mode of action of adipokinetic hormone at the sub-cellular level in potentiating anti-oxidative responses in insects. - Bednářová, Andrea (Jihočeská univerzita, 2015)
Adipokinetic hormones (AKHs) are neuropeptides from the arthropod AKH/RPCH (adipokinetic hormone/ red pigment concentrating hormone) family. The typical AKH is an octa-, nona- or decamer that is synthesized, stored and released by the neurosecretory cells of the corpora cardiaca (CC) connected to the brain and primarily involved in the mobilization of energy reserves from the fat body in insects. In addition to its well established role in energy metabolism, AKH has also been implicated to be involved in stress responses specifically to oxidative stress. Oxidative stress induced elevation of AKH levels as well as a modulation of biomarkers of oxidative damage following exogenous application of AKH have been demonstrated. However, the discrete steps involved in the mode of action of AKH in triggering an anti-oxidative response is far from clear. Given the role of AKH as a neuroendocrine factor that mediates a response to oxidative stress, the mode of action of AKH at the sub-cellular level was investigated. Using isolated central nervous system (brain) as an in vitro model, we establish that AKH can potentiate an anti-oxidative response to oxidative stress. Further, we also demonstrate that AKH uses a conserved signal transduction mechanism involving both protein kinase C (PKC) and cyclic adenosine monophosphate (cAMP) and by mobilizing both intra as well as extra-cellular Ca2+ stores to elaborate its anti-oxidative response. Finally, using the genetically tractable fruit fly Drosophila melanogaster, we demonstrate through RNAi mediated knockdown of AKH synthesis as well as overexpression of AKH using the GAL4/UAS system, that the fork-head box transcription factor (dFoXO) might function downstream of AKH signaling in its stress responsive role. These results implicate AKH as a stress hormone while offering possibilities to further identify specific regulatory mechanisms and downstream effector molecules. Since stress signaling pathways are conserved, insights obtained from such studies on insects will offer some unique avenues for understanding stress responses and related pathologies in vertebrates including humans.
Mode of action of adipokinetic hormone at the sub-cellular level in potentiating anti-oxidative responses in insects.
Keywords: Adipokinetic hormone; oxidative stress; signaling; Pyrrhocoris apterus; Drosophila melanogaster; Adipokinetic hormone; oxidative stress; signaling; Pyrrhocoris apterus; Drosophila melanogaster